INFLUENCE OF PICKS ARRANGEMENT MODE ON PERFORMANCE OF SHEARER - ZHAO LiJuan; ZHAO MingYang (Jixie qiangdu)
The drum ’s load calculation program of the staggered and sequential arrangement has been developed by MATLAB based on the shearer cutting mechanics model,which can get drum load spectrum,cutting performance parameters and the rate of lump coal under 5 typical working conditions;Shearer loading performance of two picks arrangement were analyzed by three-dimensional discrete element software PFC;The reliability of the key parts of the coal machine under different conditions has been analyzed Based on the PRO/E,MATLAB,ANSYS and ADAMS.The results show that:When the coal is cutting coal gangue,the pick should be used in sequential order,the load fluctuation is small and the reliability is high;Under normal conditions,the sequential pick arrangement of shearer can improve the lump coal rate,the cutting area will increased 1.99 times and the founder rate will increased 21% compared with the sequential type.